Institutionalist versus distortionist views of labor market reforms: An investigation into the post-liberalized manufacturing sector in India - Kumar Bhandari, Anup (2016)
Labor regulation and employment relation has been investigated in India in light of the seminal work of Besley and Burgess (2004), considering formal sector manufacturing employment as the explained variable. Empirical findings support, although not very strongly, the institutionalist view, i.e., pro-worker amendment in labour laws induces employment. Among the other factors, real wage rate has significant negative effect on employment, whereas that for real per capita developmental capital expenditure, per capita electricity generation capacity and real per capita net state domestic productis significant positive. However, effect of per capita real developmental revenue expenditure is inconclusive. In other words, although itimproves employability of workers through their human capital improvement, which is probablymetupatthe cost of worsening overallinfrastructuraldevelopment,throughreducing corresponding capital expenditure! Supporting evidence has also been provided favoring this conjecture. Doi: https://doi.org/10.1016/j.jefas.2016.06.​002